Revamping Python for an AI World: Mojo has the same syntax as Python, but runs up to 35,000 times faster. - Savage, Neil (Communications of the ACM, 2023)
The article discusses computer scientist Chris Lattner's development of the Mojo programming language (PL) which is designed to help ease the use of the Python PL (Python), and it mentions how Python is known for running slowly and is not well-suited to some forms of artificial intelligence (AI) programming. C++ language, graphics processing units (GPUs), and Python's Global Interpreter Lock element are assessed.